Наукове товариство імені Шевченка та археологічні студії на Заході України до Першої світової війни - Булик, Н.М. (Археологія і давня історія України, 2012)
У статті розглянуто процес формування академічної археологічної науки на заході України.
Головну увагу звернуто на Наукове товариства
імені Шевченка. Досліджено кілька аспектів його
археологічної діяльності, це — польові дослідження, формування музейних збірок, публікація археологічної літератури. Прослідковано наукові контакти львівських археологів з іншими вченими. В статье рассмотрен процесс формирования академической археологической науки на западе Украины. Основное внимание сосредоточено на научном
обществе имени Шевченко. Исследовано несколько
аспектов его археологической деятельности, это —
полевые исследования, формирование музейных
коллекций, публикация археологической литературы, отслежены научные контакты львовских археологов с другими учеными.
Одну из центральных позиций занимает личность Михаила Грушевского в НОШ и его вклад в
украинскую археологию в целом и, в частности, исследования эпонимного памятника высоцкой культуры. Не оставлены без внимания автора молодые исследователи В. Гребеняк, Б. Януш и их вклад в формирование Музея Общества. Отдельно проанализированы научные форумы в Украине и за рубежом, участие в них львовских археологов, а также сотрудничество между ними.
Анализ источников и литературы позволяет утверждать, что именно НОШ в преддверии Первой мировой войны заложило крепкий фундамент для развития археологической науки на западе Украины The article deals with process of academic archaeological
science formation in Western Ukraine. Main attention
is paid to Shevchenko Scientific Society. Several
aspects of its archaeological work has been researched:
field studies, museum collections formation, publication
of archaeological literature. Scientific contacts of Lviv
archaeologists with other scientists are also observed.
Person of Mykhailo Hrushevskyi occupies one of the
central positions in Shevchenko Scientific Society. As
well his contribution to Ukrainian archeology in general
is huge, and in particularly — research of eponymic site
of Vysotska culture. Young researchers such as V. Hrebenyak,
B. Janusz and their contribution to formation of
Museum of the Society are mentioned as well.
Special attention is paid to scientific forums in
Ukraine and abroad and of Lviv archaeologists participation
in them, as well as cooperation between them.
Analysis of sources and literature gives us reason to approve
that Shevchenko Scientific Society before World War I made a solid base for development of archaeological
studies in Western Ukraine.